2017
DOI: 10.3390/molecules22091539
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Activity of the Chemical Constituents of Essential Oils

Abstract: Cardiovascular diseases are a leading cause of death in developed and developing countries and decrease the quality of life, which has enormous social and economic consequences for the population. Recent studies on essential oils have attracted attention and encouraged continued research of this group of natural products because of their effects on the cardiovascular system. The pharmacological data indicate a therapeutic potential for essential oils for use in the treatment of cardiovascular diseases. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Another study showed that γ-terpinene inhibits LDL oxidation [34]. In addition, the cardiovascular activity of essential oils and their individual volatile constituents, such as α-terpineol, α-terpinene, and γ-terpinene, all have potent antioxidative capabilities resulting from the restoration of antioxidant enzyme activities [35]. Limonene, linalool, and 4-terpineol are beneficial in terms of preventing cardiovascular diseases and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that γ-terpinene inhibits LDL oxidation [34]. In addition, the cardiovascular activity of essential oils and their individual volatile constituents, such as α-terpineol, α-terpinene, and γ-terpinene, all have potent antioxidative capabilities resulting from the restoration of antioxidant enzyme activities [35]. Limonene, linalool, and 4-terpineol are beneficial in terms of preventing cardiovascular diseases and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Other benefits for treating cardiovascular disease, thus reducing the risk of atherosclerosis, include the reduction of cholesterol and triglyceride levels in plasma, in which black cumin oil achieved this reduction in rats over a period of 12 weeks, with low toxicity and no adverse effects in kidneys or liver [ 7 ]. Additionally, recent studies have demonstrated the capability of EOs to act on inflammatory and other cellular processes associated with cardiovascular diseases, by preventing the secretion of proinflammatory factors through the reduction of lipopolysaccharide (LPS) [ 30 , 31 ]. EOs may be used in both analgesics and anti-inflammatories, such as black cumin and eucalyptus oils [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most prominent and therapeutically potentially promising activities of natural monoterpenes and monoterpenoids are those on the cardiovascular system [6]. Reports on literature, here reviewed and discussed, reveal their effect on heart (rate and inotropism), systemic blood pressure (SBP), and blood vessels (direct (myogenic) and indirect (endothelium mediated)) [7][8][9][10].…”
Section: Terpenes and Terpenoidsmentioning
confidence: 99%